TOURISM IN FUNCTION OF DEVELOPMENT OF THE REPUBLIC OF SERBIA – Tourism and Rural Development - Lakićević, Marija (Hotel and Tourism Management, 2020)
Conclusions of the 5th International Scientific Conference held at the Faculty of Hotel Management and Tourism in Vrnja?ka Banja on September 4th, 2020